COMPANIES IN THE DATA WAREHOUSE IMPLEMENTATION - Marzuki MZ Marzuki (Majalah SIKOMTEK, 2010)
Data warehouse is a concept and a combination of technologies that facilitate the organization to manage and maintain historical data obtained from the system or operational applications. Data warehouses collect historical data which can then be used as a comprehensive material for management to be able to take decisions, the analysis of organizational needs, to forecasting organizations based on the data. Data warehouse allows integration of various types of data from a variety of applications or systems. This ensures the access mechanism 'one-stop shop' for management to obtain information and analyze it for the decision organizational development. Within an organization, data warehouse can be used as weapons in competing. This paper will discuss the implementation of data warehouse within the company.